2011
DOI: 10.1056/nejmoa1013911
|View full text |Cite
|
Sign up to set email alerts
|

Earlier versus Later Start of Antiretroviral Therapy in HIV-Infected Adults with Tuberculosis

Abstract: Background Tuberculosis remains an important cause of death among patients infected with the human immunodeficiency virus (HIV). Robust data are lacking with regard to the timing for the initiation of antiretroviral therapy (ART) in relation to the start of antituberculosis therapy. Methods We tested the hypothesis that the timing of ART initiation would significantly affect mortality among adults not previously exposed to antiretroviral drugs who had newly diagnosed tuberculosis and CD4+ T-cell counts of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
436
6
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 552 publications
(487 citation statements)
references
References 27 publications
33
436
6
12
Order By: Relevance
“…In patients with pulmonary TB early ART initiation is associated with improvements in AIDS-free survival, particularly in patients with low baseline CD4 counts 27 . In patients with HIV-associated TBM, however, our previous study suggested that immediate ART did not result in a survival benefit, but was associated with an increase in severe adverse events 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pulmonary TB early ART initiation is associated with improvements in AIDS-free survival, particularly in patients with low baseline CD4 counts 27 . In patients with HIV-associated TBM, however, our previous study suggested that immediate ART did not result in a survival benefit, but was associated with an increase in severe adverse events 28 .…”
Section: Discussionmentioning
confidence: 99%
“…All HIV‐infected children diagnosed with TB should also be started on ART; however, the optimal timing of ART initiation depends on the degree of immunocompromise. Adult RCTs showed significant reduction in mortality and progression to AIDS with earlier ART in patients with CD4 counts < 50 cells/μl (Starting ART at 3 Points in TB (SAPIT) 162, Cambodian Early versus Late Introduction of Antiretrovirals (CAMELIA) 163 and Immediate Versus Deferred Start of Anti‐ HIV Therapy in HIV ‐Infected Adults Being Treated for Tuberculosis (STRIDE) 164). A retrospective study in South African children, most of whom were severely immunocompromised with median CD4 percentage < 12%, also showed that delay of ART for longer than 2 months was associated with increased mortality and worse virological response 165.…”
Section: Coinfectionsmentioning
confidence: 99%
“…Les co-infections restent un problème majeur, en particulier la tuberculose et les hépatites virales, aussi bien au Nord qu'au Sud. L'étude ANRS/NIH Camelia [6], réalisée au Cambodge, avait ouvert la voie à la prise en charge optimale de la co-infection VIH et tuberculose. Dans le domaine des hépatites virales, nous sommes en pleine révolution en matière de traitement de l'hépatite C, avec l'arrivée d'une nouvelle classe de molécules, les « directacting antivirals » (DAA), qui vont permettre à court/moyen terme de se passer de l'interféron pégylé.…”
Section: Quels Enjeux De Recherche Trente Ans Après L'identification unclassified